Investigation of Amounts of Vitamins A, E, C, ?-carotene, Lycopene, Glutathione and Malondialdehyde in Red Fruit Pyracantha Coccinea Roemer var. Lalandi - Çöteli, Ebru; Karataş, Fikret (Fırat University, 2017)
In this study, the amounts of vitamin A, vitamin E, vitamin C, ?- carotene, lycopene, reduced and oxidized form of glutathione (GSH, GSSG) with malondialdehyde (MDA) in plant fruits of Pyracantha coccinea Roemer var. lalandi were determined by using High Performance Liquid Chromatography. The amount of vitamin A, vitamin E, vitamin C, ?- carotene, lycopene, GSH, GSSG and MDA in plant fresh fruits of Pyracantha coccinea Roemer var. lalandi were obtained to be 0.15±0.03; 0.22±0.04; 12.10±0.96; 37.31±3.61; 10.67±2.41; 200.81±30.15, 47.53±5.45 and 7.60±0.89 ?g/g respectively. The GSH/GSSG ratio is 4.23 ± 0.35 was observed. It can be said that Pyracantha coccinea Roemer var. lalandi plant fruits are good source of Glutathione (GSH, GSSG), vitamin C, ?-carotene and lycopene. Generaly Pyracantha coccinea Roemer var. Lalandi is planted as an ornamental plant but from these findings suggest that the fruit of this plant might be useful source of antioxidant

Bu çalışmada, kırmızı meyveleri olan Ateş Dikeninde (Pyracantha coccinea Roemer var. lalandi) A vitamini, E vitamini, C vitamini, ?- Karoten, Likopen, indirgenmiş glutatyon (GSH), yükseltgenmiş glutatyon (GSSG) ve malondialdehit (MDA) miktarları Yüksek Performanslı Sıvı Kromatografisi (HPLC) ile belirlendi. Bu bitkinin taze meyvesindeki A, E, C vitaminleri, ?-karoten, Likopen, GSH, GSSG ve MDA miktarları sırası ile 0.15±0.03 ?g/g; 0.22±0.04 ?g/g; 12.10±0.96 ?g/g; 37.31±3.61 ?g/g; 10.67±2.41 ?g/g; 200.81±30.15 ?g/g, 47.53±5.45 ?g/g ve 7.60±0.89 ?g/g olduğu belirlendi. GSH/GSSG oranın ise 4.23±0.35 olduğu gözlendi. Sonuç olarak elde edilen bulgulardan; ateş dikeni (Pyracantha coccinea Roemer var. Lalandi) bitkisinin meyvesi glutatyon (GSH, GSSG), ?- karoten ve likopen miktarları açısından iyi olabileceği söylenebilir. Ayrıca süs bitkisi olarak ekilen bu bitkinin meyvelerinin antioksidan özellikte olduğu ve bu meyvelerin halk arasında kullanımının yararlı olabileceği düşünülmektedir
Ateş Dikeninin (Pyracantha coccinea Roemer var. lalandi) Kırmızı Meyvelerindeki A, E, C Vitamini, ?-Karoten, Likopen, Glutatyon ve Malondialdehit Miktarlarının Araştırılması